Problemas Elípticos Assintoticamente Lineares - DAMKE, Caíke da Rocha (2012)
In this dissertation we analyze questions of existence and multiplicity of solutions for Dirichlet problem in the asymptotically linear case. To obtain our main results we use variational methods, such as Montain Pass Theorem and Linking Theorem.Moreover, we use the Liapunov-Schmidt reduction.